Cambridge handbook of linguistic code-switching - Bullock, Barbara E.; Toribio, Almeida Jacqueline, 1963- (Cambridge handbooks in language and linguistics., 2009)
Code-switching, the alternating use of two languages in the same stretch of discourse by a bilingual speaker, generates a great deal of pointed discussion in the public domain. This handbook provides a guide to this bilingual phenomenon, drawing on empirical data from a wide-range of language pairings.